미국 앨라배마 주 고교학점제에서 과학 교과의 특징 - 정다은; Daeun Jang; 박종석; Jongseok Park (과학교육연구지, 2024)
고등학교 교육의 혁신을 위한 고교학점제 도입에는 여러 가지 기대와 우려가 있다. 고교학점제에서 과학 교과 운영의 우려되는 점을 보완하기 위해 고교 학점제를 운영하고 있는 미국 앨라배마 주 과학과 교육과정의 특징을 분석하여 시사점을 찾아보았다. 미국 앨라배마 주의 과학과 교육과정, 교육과정 안내서, 매디슨 학교 시스템의 고등학교 교육과정 목록을 분석한 결과 첫째, 과학 과목을 다양하게 개설하고 있고 무학년제로 운영되고 있다. 둘째, 9~12학년 모든 학생들에게 대학과 진로를 위한 필수적인 준비를 제공하고 있다. 셋째, 여러 학년 수준에 걸쳐 동일한 학문적 핵심 아이디어를 논리적으로 다루고 있다. 넷째, 과학 및 공학적 소양과 문해력을 높이기 위해 학제 간 연결을 중요시하고 있다. 이러한 결과로부터 우리나라 고교학점제에서 과학 교과 운영에 주는 시사점은 첫째, 미국에 비해 교과목의 다양성이 부족하므로 다양한 교과목 개설이 필요하다. 둘째, 학생들이 진로에 따라 과학 과목을 선택하기 쉽도록 진로별 이수 체계의 안내가 필요하다. 셋째, 과목 간 부담을 줄이기 위해 과학 과목의 위계 설정을 고려해야 한다. 넷째, 학생들의 과학적 소양 및 문해력을 길러주기 위한 다른 과목과의 학제 간 연결을 고려해야 한다. 이러한 시사점을 토대로 우리나라의 고교학점제에 과학 교과의 적절한 운영 방안이 모색될 필요가 있다. There are many expectations and concerns regarding the introduction of the high school credit system as an educational innovation. To address concerns about the management of science courses in the high school credit system, we analyzed the characteristics of Alabama’s science curriculum to identify potential implications. By analyzing Alabama’s science curriculum, curriculum guide, and high school curriculum catalog of Madison City Schools, we found that, first, the system offers a variety of science subjects and operates on a non-graded basis. Second, the curriculum provides essential college and career preparation for all students in grades 9~12. Third, it consistently covers the same academic core ideas across grade levels in a logical progression. Fourth, it emphasizes interdisciplinary connections to enhance science and engineering literacy. The implications of these findings for managing science courses in Korea's high school credit system are, first, that Korea’s system lacks course diversity compared to the U.S., making it is necessary to offer a wider variety of courses. Second, students should be guided to choose science subjects aligned with their career paths. Third, a hierarchy of science subjects should be established to reduce the burden between courses. Fourth, consideration should be given to interdisciplinary connections with other subjects to foster students' scientific literacy. Based on these suggestions, it is necessary to explore the appropriate provision of science courses in the Korean high school credit system.